Alasan Rusia Melibatkan Diri dalam Konflik Bersenjata Suriah Tahun 2011-2015 - Kusumastuti, Dita Arum; Utomo, Tri Cahyo; Hanura, Marten (Journal of International Relations, 2017)
Arab Spring which was happened in 2011 had ceated nationwide protest movement of the Syrian people to throw the regime of the President Bashar Al Assad. The conflict that was, at first,only protest then turned into armed conflict where the government, opposition and terrorism groups such as ISIS and Jabhat Al Nusra involved. The number of the deaths caused by the conflict were then called by the UN as crime against humanity. The UN initiated Geneve Peace Talks as an agenda to hold a political transition towards Bashar Al Assad’s regime. The effort was rejected by Russia Federation. In 2013, the U.S. and its alliance deployed its miltary forces in Syria to suport opposition group while in 2015 Russia then responded to the U.S. action by deploying its military troops in order to support the regime of Bashar Al Assad. This research is aimed to explain the motives of why Russia involved in the Syrian armed conflict. The research used qualitative method and Offensive Realism Theory by John J. Mearsheimer. The result of this research is that the involvement of Russia was meant to exercise its geopolitical influence in the Middle East and to repress the expansion of U.S. influence in Syria.